Socio-economic impact of African swine fever on small-holder farms a long the Kenya-Uganda border - Nantima, Noelina (Kampala, 2015)
Unpublished thesis (PHD) - Makerere University, 2015
Includes bibliographical references (p. 102-112)
Keywords: Africa swine fever -- Kenya-Uganda border; Farmers -- Economic conditions -- Kenya-Uganda border; Farmers -- Social conditions -- Kenya-Uganda border